AB0814 Online Patient Information Resources on Gout Provide Inadequate Information and Minimal Emphasis on Potentially Curative Urate Lowering Treatment. (15th July 2016) - Jiménez-Liñán, L.; Edwards, L.; Abhishek, A.; Doherty, M.
Abstract : Background: Nowadays patients use the internet to find more about their disease and its management. The accuracy of online gout patient information resources has not been examined before. Objectives: To assess the content, accuracy and readability of freely available online patient information resources against the current understanding of gout. Methods: An internet search was carried out to identify online gout patient information resources from the United States of America (USA), United Kingdom (UK), Australia and Canada in October 2015. Websites aimed at healthcare professionals, those requiring a paid subscription, or focussed on a specific aspect of gout were excluded. Information provided in the websites was compared against 15 key points. If information on a key point was regarded as present, it was classified on a 1–3 Likert Scale (1-inaccurate, 2-acceptable information with some inaccuracy and 3-acurate). Readability was assessed using Flesch-Kincaid Reading Ease score. Fifteen randomly selected websites were reviewed by a binder second reviewer. Results: Eighty-five websites (30 provided by a medical and/or healthcare organisation were selected). Information was provided for a mean (SD) 7.73 (2.85) of 15 key points overall. The websites were more likely to contain information on risk-factors than on treatment of gout (p<0.001). More than 50% provided no information, or had inaccuracies regarding the pathogenesis of gout and over 75% of websites had no or inaccurate information on the role of ULT. Most websites highlighted information on dietary and lifestyle modifications for treating gout and did not emphasise ULT and its potential for cure. The two raters agreed in 80% of occasions on whether information on a particular question was present or not ( k 0.60). The majority of websites were difficult to read, with information in 68% websites rated as at least fairly difficult. Conclusions: Most of the patient information on gout available online is inaccurate and commonly over emphasises the use of dietary and lifestyle changes as a way of managing gout. The importance of ULT in managing gout and the potential for gout being curable with long-term ULT are not explained well. Moreover, most websites were difficult to read and most on-line resources had inaccuracies regarding the pathogenesis and treatment of gout. Disclosure of Interest: None declared